Helix Light Vortex Theory (HLV) -Symbolic Grammar G-HLV Framework - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
The Helix-Light-Vortex (HLV) Theory dares to challenge the very foundations of physics, proposing a universe built on emergent geometry and information. Traditional mathematics often struggles to fully capture concepts like topological interactions and recursive time, limiting our understanding. Our new paper introduces G_HLV, a novel Symbolic Grammar that serves as the HLV Theory's native operating system, uniquely designed for this reality. This revolutionary language unlocks the deep physics behind emergent properties, where everything from mass to spin arises from underlying topological rules. Crucially, we demonstrate a rigorous derivation of the Feynman Path Integral directly within G_HLV, ensuring that quantum dynamics are fully preserved. This groundbreaking approach provides a formal, intuitive, and potentially simulable description of a universe fundamentally based on discrete space-bits and dynamic spiral time. It fundamentally redefines how we model reality, moving beyond point particles to an interconnected tapestry of wave resonances. The implications are profound, offering new insights into cosmology, matter, and even consciousness. This isn't just a new theory; it's a new way to do physics. Dive in and discover the universe's true operating system. © 2025 Marcel Krüger — CC BY 4.0 https://creativecommons.org/licenses/by/4.0/
The Helix-Light-Vortex (HLV) Theory dares to challenge the very foundations of physics, proposing a universe built on emergent geometry and information. Traditional mathematics often struggles to fully capture concepts like topological interactions and recursive time, limiting our understanding. Our new paper introduces G_HLV, a novel Symbolic Grammar that serves as the HLV Theory's native operating system, uniquely designed for this reality. This revolutionary language unlocks the deep physics behind emergent properties, where everything from mass to spin arises from underlying topological rules. Crucially, we demonstrate a rigorous derivation of the Feynman Path Integral directly within G_HLV, ensuring that quantum dynamics are fully preserved. This groundbreaking approach provides a formal, intuitive, and potentially simulable description of a universe fundamentally based on discrete space-bits and dynamic spiral time. It fundamentally redefines how we model reality, moving beyond point particles to an interconnected tapestry of wave resonances. The implications are profound, offering new insights into cosmology, matter, and even consciousness. This isn't just a new theory; it's a new way to do physics. Dive in and discover the universe's true operating system. © 2025 Marcel Krüger — CC BY 4.0 https://creativecommons.org/licenses/by/4.0/